Consumo de álcool e adiposidade abdominal : resultados do estudo longitudinal de saúde do adulto-ELSA-Brasil - Torres, Gabrielle Guidoni (2015)
The accumulation of abdominal fat have a positive association with cardiovascular events, blood pressure and metabolic changes. Among the risk factors for increased abdominal obesity is the high consumption of alcohol, particularly beer. The objective of this study was to identify the association between alcohol consumption (AC) and abdominal fat. This is a cross-sectional research conducted from the baseline of the Study of Adult Health Longitudinal - ELSA-Brasil, composed of 15,105 individuals (35-74 years). Anthropometric, socioeconomic and consumption of alcoholic beverages were analyzed and used for diagnosis of abdominal obesity, the cutoffs of waist circumference (WC) and waist / hip ratio (WHR) recommended by the World Health Organization. The AC was categorized into quintiles. Kolmogorov-Smirnov test was used to assess the normality of the variables. The association between anthropometric variables and the AC was evaluated using Mann-Whitney, Kruskal-Wallis and chi-square test. Linear and Poisson regression models were tested, adjusted for age, sex, BMI, smoking, physical activity, income and education. Inadequate WC was associated with higher AC in the whole sample (1.03, 95% CI 1.01 to 1.05) and men (1.05, 95% CI 1.03 to 1.08). Inadequate WHR was associated with higher AC for the total sample (1.04, 95% CI 1.01-1.06) and women (1.07, 95% CI 1.03 to 1.12). Men in the fifth quintile of beer consumption showed a greater chance 1.05 (95% CI 1.02 to 1.08) to have inadequate WC when compared to those who were in the first quintile. Among women the chance was 1.16 (95% CI 1.13 to 1.20). Men and women in the fifth quintile of consumption of beer were, respectively, 1.03 (95% CI 1.00-1.07) and 1.10 (95% CI 1.04 to 1.15) times more likely to have inadequate WHR. Wine consumption was not associated with a higher chance of having WC increased among women (β = 0.026, p <0.027). In this study, alcohol consumption was positively associated with abdominal obesity, and beer the most important contribution to increasing WC and WHR.